Anorexia nervosa—the frequency of occurrence in Polish youth, the connection with stress, auto-aggressive behaviors and the abuse of psychoactive substances - Górski, Michał; Polaniak, Renata; Całyniuk, Beata; Garbicz-Kata, Jagoda; Buczkowska, Marta; Fojcik, Joanna; Nowak, Justyna; Domagalska, Joanna (Frontiers in Psychology, 2025)
BackgroundAnorexia nervosa is an eating disorder characterized by a distorted self-image, an intense desire for weight loss, anxiety, and strict dieting. The disorder primarily affects children, adolescents, and young adults. It leads to serious health consequences and increases the risk of depression, suicidal thoughts, and addiction. The causes of the disorder are multifactorial, including genetic influences, social pressures, and emotional problems. Eating disorders are now considered a serious public health problem that requires special supervision by specialists and the development of long-term measures to reduce their incidence.ObjectiveThe objectives of the study were to determine the prevalence of anorexia nervosa among school adolescents aged 15–19; to determine the relationship between the prevalence of anorexia nervosa and the severity of school stress, the severity of family stress, the use of psychoactive substances, and the occurrence of auto-aggressive and self-destructive behavior.Materials and methodsThe group of respondents consisted of individuals aged 15 to 19 years (secondary school students). The study utilized a diagnostic interview method, along with an additional questionnaire. The author’s survey questionnaire was developed based on the diagnostic criteria for anorexia nervosa in the International Classification of Diseases, 11th Revision and Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, as well as information from scientific sources regarding stressors and auto-aggressive and self-destructive behaviors. In the statistical analysis, a significance level of α = 0.05 was adopted.ResultsThe diagnostic criteria for anorexia nervosa were met by 13.3% of respondents. 37.1% of respondents admitted to engaging in self-injurious behavior, and 13.9% reported having suicidal thoughts. The greatest risk factors for developing anorexia nervosa were female gender, high maternal education, and high levels of physical activity.ConclusionIndividuals who could be diagnosed with anorexia nervosa experienced higher levels of school stress and a greater sense of family stress compared to those who did not meet the diagnostic criteria for the disorder. Auto-aggressive and self-destructive behaviors were much more common among those with a possible diagnosis of anorexia nervosa than among those who did not meet the criteria for the disorder.